Identifying and changing cognitive vulnerability in the classroom: preliminary evaluation of CUES‐Ed, a school‐based universal cognitive behavioural early intervention service for 7–10 year olds. Issue 2 (30th November 2021) - Underwood, Raphael; Redfern, Anna; Plant, Debbie; Bracegirdle, Karen; Browning, Sophie; Jolley, Suzanne
Abstract : Background: School‐based early intervention may alleviate current emotional and behavioural problems, and, by targeting underlying vulnerability, safeguard children's future mental health. Improving on mixed outcomes to date is an international public health priority. CUES‐Ed is a classroom‐based, clinician‐led, universal cognitive behavioural programme for primary school children, designed to promote emotional literacy and regulation. Additionally, CUES‐Ed targets cognitive mechanisms implicated in the future development of mental disorder: stigmatising appraisals of emotional expression and of unusual perceptual experiences, and the tendency to jump‐to‐conclusions (JTC). We report here on fitness for purpose of our in‐service assessment of cognitive vulnerability, and change in cognitive vulnerability following CUES‐Ed and compared with a naturalistic waitlist. Methods: From 05/2017–11/2017, 960 children participated (900 CUES‐Ed; 60 naturalistic waitlist). Assessments were completed in whole classes; 732 children provided pre‐post data on all measures; 227 were missing data through absence or poor completion ( n = 1 declined assessment). Results: Relationships between baseline cognitive vulnerability measures and their components were consistent with reliable and valid assessment. Cognitive vulnerability reduced from before to after CUES‐Ed and compared with the naturalistic waitlist, for JTC (large effects) and stigmatising appraisals (small–medium effects), for all children (ESs pre‐post: 0.2–1.0; between‐group: 0.1–1.0) and vulnerable subgroups (ESs pre‐post: 0.5–1.7; between‐group: 0.2–2.0). Conclusions: Targeted cognitive vulnerability mechanisms change following CUES‐Ed. As stigmatising appraisals and JTC may increase vulnerability to future mental illness, findings suggest a promise in reducing future risk. A formally controlled research study, with longer‐term follow‐up, is required to test this. Limitations and implications for future evaluation are discussed.